Evolutionary biology as a link between religion and knowledge - Du Toit, Cornel W. (HTS Teologiese Studies / Theological Studies, 2000)
It would appear that the epistemological tradition of the West is culminating in the present science-religion debate. The evolutionary model is being used increasingly in different disciplines as a guideline to understand humans and their action in the world. The struggle for explaining the action of God has shifted from the world of history and texts to the invisible level of quantum physics and molecular biology. It seems that levels of indeterminacy in quantum mechanics and autopoietic systems offer space to explain the action of God. On the human level integrity is sought by linking the highest level of consciousness and rationality to the very basic level of molecular and genetic structures. These issues are dealt with and specific attention is given to autopoietic systems and the biological roots of rationality.
Free
Keywords: Netherdutch Reformed Church; Practical Theology; Theology; ancient Semitic and classical languages; aspects of religious studies; ministers of religion; philosophers; philosophy; scholars; sociology and ethics; theologians